2014
DOI: 10.1515/cclm-2013-0899
|View full text |Cite
|
Sign up to set email alerts
|

Serum miR-122 levels are related to coagulation disorders in sepsis patients

Abstract: Serum levels of miR-122 were correlated to the coagulation disorder in sepsis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 24 publications
0
42
0
2
Order By: Relevance
“…This miRNA is commonly considered to be liver specific, and increased serum concentrations have been reported in cases of liver injury and hepatotoxicity [63]. Increased serum levels of miR-122-5p were also reported in sepsis patients, correlating with liver damage, coagulation disorders and mortality [53,64,65]. A more recent publication by Roderburg et al, however, demonstrated that miR-122-5p expression in critically ill patients was dysregulated by hepatic injury alone, independent of an infectious state [66].…”
Section: Discussionmentioning
confidence: 99%
“…This miRNA is commonly considered to be liver specific, and increased serum concentrations have been reported in cases of liver injury and hepatotoxicity [63]. Increased serum levels of miR-122-5p were also reported in sepsis patients, correlating with liver damage, coagulation disorders and mortality [53,64,65]. A more recent publication by Roderburg et al, however, demonstrated that miR-122-5p expression in critically ill patients was dysregulated by hepatic injury alone, independent of an infectious state [66].…”
Section: Discussionmentioning
confidence: 99%
“…Compared with severe sepsis patients with normal platelet counts, the expression of miR-130a in peripheral blood monocytic cells was significantly lower in septic patients with thrombocytopenia [86]. Longitudinal samples of sepsis patients revealed a sustainable increase of miR-122 up to 14 days after admission to the intensive care unit and showed a strong correlation with antithrombin III ( R  = 0.913, p  < 0.001) [87]. To determine direct or indirect effects of miRNAs on coagulation, further mechanistic studies are required to identify crosstalk, if any, between cytokines, thrombocyte synthesis/apoptosis, and deregulation of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…miR-147b represents an endothelial barrier of protection against endotoxin-mediated inflammation by decreasing ADAM metallopeptidase domain 15 (ADAM15) expression and attenuating LPS-induced barrier dysfunction during septic challenge by bacterial LPS in endothelial cells (12). Serum levels of miR-122 have been shown to be increased in patietns with sepsis with clotting abnormalities (13). miR-133a levels have also been shown to correlate with the severity of sepsis and, at significantly higher levels, predicted an unfavorable prognosis of critically ill patients (14).…”
Section: Introductionmentioning
confidence: 99%